2020
DOI: 10.1177/1591019920973848
|View full text |Cite
|
Sign up to set email alerts
|

Stent-assisted coil embolization for an unruptured vertebral artery–posterior inferior cerebellar artery aneurysm with retrograde access via type 1 persistent primitive proatlantal artery: A case report

Abstract: Vertebral artery (VA)-posterior inferior cerebellar artery (PICA) aneurysms are rare lesions that are difficult to treat with both endovascular and surgical techniques. Tight angulation of the PICA from VA may make access to the PICA difficult from ipsilateral VA if adjunctive techniques are needed. Recently, the safety and efficacy of retrograde access have been reported. We report a case of endovascular treatment for a VA-PICA aneurysm with a stent-assisted technique using retrograde access via contralateral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Up and over retrograde access via the contralateral vertebral artery offers another method for addressing incomplete VAI treatment that avoids challenging and more invasive surgical reoperation. Reports of retrograde vertebral access exist for other indications, most often for vertebral or PICA aneurysms that cross midline or cannot be accessed ipsilaterally [15][16][17][18][19] for reasons including subclavian stenosis 19 . However, this technique has only rarely been applied in the setting of penetrating trauma 20,21 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Up and over retrograde access via the contralateral vertebral artery offers another method for addressing incomplete VAI treatment that avoids challenging and more invasive surgical reoperation. Reports of retrograde vertebral access exist for other indications, most often for vertebral or PICA aneurysms that cross midline or cannot be accessed ipsilaterally [15][16][17][18][19] for reasons including subclavian stenosis 19 . However, this technique has only rarely been applied in the setting of penetrating trauma 20,21 .…”
Section: Discussionmentioning
confidence: 99%
“…Retrograde vertebral access has been performed for other indications, most often for vertebral or posterior inferior cerebellar artery aneurysms that cross the midline or cannot be accessed ipsilaterally for reasons that include subclavian stenosis. 15 , 16 , 17 , 18 , 19 However, this technique has only rarely been applied in the setting of penetrating trauma. 20 , 21 Retrograde vertebral access can be especially useful for polytrauma patients who are too unstable for time-consuming, complex, open surgery.…”
Section: Discussionmentioning
confidence: 99%
“… 9) There have been reports of endovascular treatment of aneurysms via PPPA and stent-assisted coiling for VA–PICA aneurysm by placing a stent through the contralateral PPPA. 3 , 10) …”
Section: Discussionmentioning
confidence: 99%
“… 1 , 2) A previous study has reported finding a PPPA unintentionally during endovascular treatment and utilizing it as an access route. 3) …”
Section: Introductionmentioning
confidence: 99%
“…Unstable results of surgical treatment of VA stenosis are due to the lack of an optimal diagnostic algorithm to determine the nature, degree, and level of cervical spine disorders as the basis for the type of surgical intervention selection in critical vasoconstriction [5][6][7][8][9][10][11][12][13][14][15]. The system of indications for surgical treatment in tortuosity of segment VI of the VA and the issues of differentiated use of various techniques of reconstructive surgery and prediction of their results are insufficiently developed.…”
Section: Introductionmentioning
confidence: 99%